Evidence on effectiveness of intensity‐modulated radiotherapy versus 2‐dimensional radiotherapy in the treatment of nasopharyngeal carcinoma: Meta‐analysis and a systematic review of the literature. (17th June 2015) - Co, Jayson; Mejia, Michael Benedict; Dizon, Janine Margarita
Abstract: Background: Current management of nasopharyngeal carcinoma (NPC) uses radiotherapy (RT) as the curative treatment modality. Radiation delivery techniques for NPC can be achieved using 2D conventional RT or intensity‐modulated radiotherapy (IMRT). Methods: A systematic review and meta‐analysis of the literature was undertaken to assess the effectiveness of IMRT versus 2D conventional RT in primary treatment of NPC. Results: IMRT showed better results than 2D conventional RT in terms of local control, regional control, and overall survival, but when stratified, only in T4, N2, and stage III were the differences that were seen. Objective saliva measurements and physician‐graded xerostomia were better in IMRT. However, patient‐reported xerostomia showed minimal improvement only in IMRT. The evidence of superiority of IMRT over 2D conventional RT is not clear. Conclusion: In the absence of more clinical data demonstrating the superiority of IMRT in the treatment of nasopharyngeal carcinoma, 2D conventional RT seems to be a reasonable treatment option, especially in limited resource settings. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2130–E2142, 2016